Treasury Auctions and Secondary Market Dynamics. An Analysis Based on the MTS Market for Italy. - Gianluca Cafiso (Center for Economic Studies and ifo Institute (CESifo), 2015)
Auctions of government bonds are the main allotment method used by the Treasury of advanced economies. Previous research has found that auctions have an influence on the market yield days before they take place, and underpricing is usually spotted when their outcome is compared with contemporaneous market quotes. The objective of this research is to investigate deeper and more accurately these two findings by taking Italy as a case study. Our results question the so-called auction cycle and do not signal underpricing when a perfect matching between the auctioned bond and the market quote used is ensured.
Keywords: G12; G14; G18; 330; primary market; secondary market; MTS market; treasury auctions; government bonds; market micro-structure; regime volatility